SURGICAL TREATMENT OF CEREBRAL PALSY - KH.T. GANIEV; A.A. RAZZOKOV (Avicenna Tajik State Medical University, 2024)
Objective: To improve surgical treatment outcomes of spastic cerebral palsy (SCP) with lower extremities involvement Methods: The results of surgical treatment of 208 children aged 3 to 14 years with SCP affecting the lower extremities were analyzed. Depending on the treatment tactics, the patients were divided into two groups. The main group included 105 (50.5%) patients who underwent surgery in addition to continuous complex conservative treatment. The control group included 103 (49.5%) children who were operated against the background of unsystematic and incomplete course of conservative therapy with unsystematic drug administration Results: The surgical treatment tactics were optimized by considering the patient's age, types and combinations of contractures and deformities, enhanced surgical indications, muscle spasticity, and gait disturbances. Improvements have been made in identifying the need to correct particular contractures and deformities. Alongside the commonly used techniques, several enhanced approaches for surgical correction of contractures and deformities have been suggested. In creating efficient surgical strategies, the focus was initially on conducting surgeries on soft tissues. Bone surgeries were carried out only if soft tissue surgeries were unsuccessful. Considering the factors mentioned above, there have been enhancements in the guidelines for multilevel surgical procedures, which may be implemented in single or multiple stages, considering secondary deformities. The scale proposed during the study was used to evaluate long-term treatment outcomes. Implementing the above approach contributed to a statistically significant improvement in long-term outcomes in the main group compared to the control group (72.5±4.7 and 61.2±3.6 points, respectively; p<0.001). Based on objective data, it was found that the rates of positive outcomes (scoring above 70 points) were significantly higher in the main group compared to the control group (64.4% and 11.8%, respectively, p<0.001). Conversely, the control group showed a predominance of satisfactory outcomes (scoring 61 to 70 points) in comparison to the main group (27.7% versus 65.6%, p<0.001). The main group had a statistically significantly lower rate of unsatisfactory results than the control group (7.9% and 22.6%, respectively, p<0.01). Conclusion: The study's findings demonstrated a statistically significant improvement in the long-term outcomes of treating SCP by implementing enhanced treatment strategies. Performing surgical procedures based on optimized indications leads to favorable outcomes in 92.1% of patients